Code mixing analysis used in Ria SW youtube channel - Silma Novasabilla Pradinta; Rosita Ambarwati; Yuli Kuswardani (Universitas PGRI Madiun, 2022)
This study focuses about the phenomena of code mixing in Ria SW Youtube Channel because she is a food vlogger who often mix the language with English to interpret the clear explanation about food so it can be understood by others. The objectives of this study are to describe the type of code mixing and the social factors influence the used of code mixing in Ria SW Youtube Channel. The research approach used to analyze the data is descriptive qualitative approach. As the theory used, the writer described based on the theory of Hoffman (1991) to analyze the types of code mixing and the theory of Weinreich (1963) to analyze the factors of code mixing. The writer collected the data from three videos which are Taipei Street Food #02, Unique Food in Singapore #05, and Hello Bali #01. The result demonstrates that there are three types of code mixing which are intra-sentential code mixing about 132 data or 75%, intra-lexical code mixing about 30 data or 17%, and involving a change of pronunciation about 14 data or 8%. Intra-sentential code mixing is the dominant occurrence of code mixing used in Ria SW Youtube Channel because the speaker inserts English words in the middle or at the end of the utterances. Furthermore, there are five social factors of code mixing which are low frequency words about 138 data or 78%, oversight about 21 data or 12%, synonym about 8 data or 5%, pernicious homonym about 6 data or 3%, and social value about 3 data or 2%. The dominant social factor influenced the use of code mixing in Ria SW Youtube Channel is low frequency words because the term or word in the English language is easier to remember and have stable meaning.